2009
DOI: 10.1038/hr.2009.115
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of autonomic cardiovascular control following acute alpha-adrenergic treatment in chronic hypotension

Abstract: Chronic low blood pressure is typically accompanied with symptoms such as fatigue, reduced drive, dizziness, headaches and cold limbs. Alterations in autonomic cardiovascular regulation are assumed to be involved in the etiology of this condition, that is, increased baroreflex sensitivity (BRS) as well as reduced sympathetic and augmented parasympathetic influences on cardiovascular regulation. In this study, the acute effects of the blood pressure-enhancing alpha-adrenergic agonist, midodrine, on autonomic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…Alterations in autonomic cardiovascular regulation appear to be the cause. A diminished general sympathetic tone and high levels of vagal activity in hypotensives are concepts repeatedly reported in several recent studies (Duschek et al, 2009(Duschek et al, , 2005Schandry, 2006, 2007). To support the role of the Neurovegetative system, these authors mainly referred to studies showing that hypotensives, compared to normotensives, exhibited faster habituation of electrodermal responses to tones (Fredrikson et al, 1990); reduced subjective symptoms and high blood pressure following the administration of substances (Bismarck and Rust, 1982); reduced electrodermal activity (Richter-Heinrich et al, 1971); and augmented respiratory sinus arrhythmia (Cadalbert, 1997).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Alterations in autonomic cardiovascular regulation appear to be the cause. A diminished general sympathetic tone and high levels of vagal activity in hypotensives are concepts repeatedly reported in several recent studies (Duschek et al, 2009(Duschek et al, , 2005Schandry, 2006, 2007). To support the role of the Neurovegetative system, these authors mainly referred to studies showing that hypotensives, compared to normotensives, exhibited faster habituation of electrodermal responses to tones (Fredrikson et al, 1990); reduced subjective symptoms and high blood pressure following the administration of substances (Bismarck and Rust, 1982); reduced electrodermal activity (Richter-Heinrich et al, 1971); and augmented respiratory sinus arrhythmia (Cadalbert, 1997).…”
Section: Introductionmentioning
confidence: 75%
“…Recent intriguing results obtained by Duschek et al (2009), suggested a sympathetic inhibition and a parasympathetic activation after drug application in essential hypotension. However, this data does not directly support a constitutional alteration in autonomic cardiac control, but rather suggests a specific counter-regulatory autonomic response to the application of an alpha-adrenergic drug.…”
Section: Introductionmentioning
confidence: 95%
“…Evidence now exists for a strong association between reduced HRV and psychotropic drugs with anticholinergic properties includeing antipsychotics and tricyclic antidepressants 4,8-10,24,31. In addition, the effects of alpha adrenoceptor modulation on HRV via sympathetic and parasympathetic inputs were reported 19,32,33. Therefore, a significant reduction in pNNx statistics is assumed to be explicitly as-sociated with the direct effects of clozapine, although the psychotic symptom itself, might contribute to the decreased heart rate dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tzeng et al (2010a) showed an inverse relationship between cardiac baroreflex sensitivity and dCA, suggesting the presence of compensatory interactions between peripheral blood pressure and central CBF control mechanisms, directed to optimizing CBF control. Such interactions may account for the divergent changes in CA and baroreflex sensitivity seen with normal aging, and in clinical conditions such as spontaneous hypertension , autonomic failure (Hetzel et al, 2003) and chronic hypotension (Duschek et al, 2009). Some evidence also indicates that free radicals -particularly superoxide anion observed in pathologies such as ischemic and traumatic brain injury -causes impaired CA and increased basal CBF through activation of potassium channels within vascular smooth muscle cells (Zagorac et al, 2005).…”
Section: Cerebral Autoregulationmentioning
confidence: 98%